Effects of media framing in news articles on blame attributional attitudes towards rape victims - Chen, Sylvia Lixia (2019)
Victim blaming, which is the tendency to hold the victim responsible for the crime, was well studied in the context of rape and sexual violence (Grubb & Harrower, 2009). However, the focus was usually placed on gender and rape myth acceptance (RMA) of the observer and circumstances of the individual rape incident (stranger rape or date rape). This study, therefore, investigated the effects of type of media framing in news articles covering rape incidents on victim-blaming attitudes. Two types of framing, episodic and thematic framing, and their effects on victim and perpetrator blame, perception of victim’s personality and RMA were examined. 142 university students (63 males, 79 females) were randomly assigned to one of the three news articles on a rape case and were asked to provide responses before and after reading. Contrary to what was hypothesised, results showed that participants in the thematic condition attributed significantly less blame to the perpetrator than those in the episodic condition. Additionally, RMA was found to significantly predict both victim and perpetrator blame as expected. Participants with higher RMA would attribute more blame to the victim and less to the perpetrator. Results revealed that university students in Singapore may have moderate levels of RMA and a somewhat negative impression of rape victims. Given that these could suggest the prevalence of victim-blaming attitudes in Singapore, these findings are concerning and warrant the attention of the government. Implications on media coverage of sexual offences and pre-existing efforts to raise awareness about victim blaming were discussed.